Faktor-faktor yang Memengaruhi Produksi Hasil Tangkapan Ikan dengan Menggunakan Alat Tangkap Gillnet di Kelurahan Kampung Nelayan - Nurcholifah, Nadilla; Akmal, Akmal; Hariski, M; H, Afriani; Idris, Nahri; Magwa, Rizky Janatul (Universitas Galuh, 2025)
The dominant fishing gear operated by fishermen in Kampung Nelayan Village is a gillnet. Fishing with gillnets to be optimal needs to pay attention to the production factors used. The purpose of this study is to find out the factors that affect the production of fish catches using gillnets in Kampung Nelayan Village, Tungkal Ilir District, Tanjung Jabung Barat Regency. The method used in this research is a survey, a sampling method using purposive sampling based on the criteria, namely gillnet fishermen who use 0-5 GT boats and are still actively fishing with the number of samples used is 41 fishermen. The data analysis used is multiple linear regression. The results of the study show that cumulatively all the factors used have a significant influence on the production of catches, but partially the factors that affect the production of fish catches using gillnet fishing equipment are only the length of the net, the height of the net, the size of the net and the distance of the fishing area, while the strength of the machine and the length of soaking the net do not have a significant influence on the production of fish catches with using gillnet fishing gear in the Kampung Nelayan Village.